Dryland Sunflowers In Western Kansas— Confectionary, W-S-F Rotation - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on typical production of dryland sunflower, both confectionary and oil type, in western Kansas.
MF937_1995_10
Keywords: MF937; Economics; Crops; MF